A emergência do novo coronavírus e a “lei de quarentena” no Brasil / The emergency of the new coronavirus and the “quarantine law” in Brazil - Ventura, Deisy de Freitas Lima; Aith, Fernando Mussa Abujamra; Rached, Danielle Hanna (Revista Direito e Práxis, 2021)
DOI: 10.1590/2179-8966/2020/49180 Resumo A Lei n. 13.979, de 6 de fevereiro de 2020, regula medidas de saúde pública relacionadas à emergência do novo coronavírus com alto potencial restritivo de direitos fundamentais, inclusive a quarentena e o isolamento. Esta análise crítica aborda a dimensão internacional da emergência, além da tramitação casuística e antidemocrática da lei brasileira. Com base na legislação epidemiológica em vigor, escrutina estas medidas excepcionais e as salvaguardas à sua implementação. Palavras-chave: Quarentena; Coronavírus; Emergência Internacional Abstract Law no. 13,979, of February 6, 2020, regulates public health measures related to the emergence of the new coronavirus with high potential to restrict fundamental rights, including quarantine and isolation. This critical analysis addresses the international dimension of the emergency, and the casuistic and anti-democratic procedure of the Brazilian law. Based on the epidemiological legislation in force, it scrutinizes restrictive measures and safeguards for its implementation. Keywords: Quarantine; Coronavirus; International Emergency